Group Interprofessional Chronic Pain Management in the Primary Care Setting: A Pilot Study of Feasibility and Effectiveness in a Family Health Team in Ontario - Ricardo N Angeles; Dale Guenter; Lisa McCarthy; Martha Bauer; Miriam Wolfson; Maria Chacon; Lana Bullock (Pain Research and Management)
BACKGROUND: Approximately 18.9% of Canadians live with chronic pain. Primary care reform in Ontario presents unique opportunities to assess approaches to help these patients.